Global research trends on COVID-19 and stroke: A bibliometric analysis - Zeng, Youjie; Cao, Si; Yang, Heng (Frontiers in Neurology, 2023)
Background The pandemic of COVID-19 has had a profound influence on worldwide healthcare systems. Our study aimed to conduct a bibliometric analysis to explore the impact of COVID-19 on stroke and to highlight the major research trends in this field. Methods We searched the original articles and review articles regarding COVID-19 and stroke from the Web of Science collection (WOSCC) database between January 1, 2020 and December 30, 2022. Subsequently, we performed bibliometric analyses and visualization using VOSviewer, Citespace, and Scimago Graphica. Results A total of 608 original articles or review articles were included. JOURNAL OF STROKE and CEREBROVASCULAR DISEASES published the most studies on this subject (n = 76), while STROKE was the source of the most-cited references (n = 2,393). The United States is the most influential country in this field, with the highest number of publications (n = 223) and citations (n = 5,042). Shadi Yaghi from New York University is the most prolific author in the field, while Harvard Medical School is the most prolific institution. In addition, through keyword analysis and reference co-citation analysis, three major research topics were identified: (i) the impact of COVID-19 on stroke outcomes (including risk factors, clinical characteristics, mortality, stress, depression, comorbidities, etc.); (ii) the management and care of stroke patients during the COVID-19 pandemic (including thrombolysis, thrombectomy, telemedicine, anticoagulation, vaccination, etc.); and (iii) the potential relationship and pathological mechanism between COVID-19 and stroke (including renin-angiotensin system activation, SARS-CoV-2 virus-induced inflammation leading to endothelial impairment, coagulopathy, etc.). Conclusion Our bibliometric analysis provides a comprehensive overview of the current state of research on COVID-19 and stroke and highlights key areas of focus in the field. Optimizing the treatment of COVID-19-infected stroke patients and elucidating the underlying pathogenic mechanisms of COVID-19 and stroke co-morbidity are key areas of future research that will be beneficial in improving the prognosis of stroke patients during the ongoing COVID-19 epidemic.